Treating Cutaneous T-Cell Lymphoma with Highly Irregular Surfaces with Photon Irradiation Using Rice as Tissue Compensator - Majithia, Lonika; Rong, Yi; Siddiqui, Farzan; Hattie, Todd; Gupta, Nilendu; Weldon, Michael; Chakravarti, Arnab; Wong, Henry K.; Porcu, Pierluigi; Xu-Welliver, Meng (Frontiers in Oncology, 2015)
Purpose: Cutaneous T-cell lymphoma (CTCL) is known to have an excellent response to radiotherapy, an important treatment modality for this disease. In patients with extremity and digit involvement, the irregular surface and depth variations create difficulty in delivering a homogenous dose using electrons. We sought to evaluate photon irradiation with rice packing as tissue equivalence and determine clinical tolerance and response. Materials and Methods: Three consecutive CTCL patients with extensive lower extremity involvement including the digits were treated using external beam photon therapy with rice packing for tissue compensation. The entire foot was treated to 30-40 Gy in 2-3 Gy per fraction using 6 MV photons prescribed to the mid-plane of an indexed box filled with rice in which the foot was placed. Optically stimulated luminescence dosimeter (OSLD) was used for dose measurement to determine the dose deposition to the skin surface. Treatment tolerance and response were monitored with clinical evaluation. Results: All patients tolerated the treatment without treatment breaks. Toxicities included grade 3 erythema and desquamation with resolution within 4 weeks. No late toxicities were observed. All four treated sites had partial response (PR) by the end of the treatment course. All patients reported improved functionality after treatment, with less pain, drainage, or swelling. No local recurrence has been observed in these patients with a median follow-up time of 14 months. Conclusion: Tissue compensation with rice packing offers a convenient, inexpensive and reproducible method for the treatment of CTCL with highly irregular surfaces.